Set Up and Calibration of a Spatial Tool for Simulating River Discharge of Western Java in Recent Decades: Preliminary Results and Assessments - Poerbandono Poerbandono; Philip J. Ward; Miga M. Julian (Institute for Research and Community Services, Institut Teknologi Bandung, 2009)
This paper discusses a study of the application of global spatiotemporal climate datasets and the hydrological model STREAM (Spatial Tools for River Basin Environmental Analysis and Management Options). In the study, set up and calibration of STREAM for the reconstruction of monthly discharge for several locations in the western part of Java, Indonesia, for the period 1983 -2002 are carried out. The set up includes the preparation of monthly precipitation and temperature datasets, a digital elevation model of the domain being studied, and maps of land cover and soil water holding capacity. Discharge observations from six stations located mostly in the upper parts of major watersheds in the domain are used to calibrate the model by comparing simulated and observed discharge variables. The model performs reasonably well. Comparison between computed and observed mean monthly discharges yield correlation coefficients ranging from 0.72 to 0.93. The computed mean annual discharge in five out of six observation stations ranges between -8 and 5% with respect to the mean annual observed discharge. This study offers a tool which can be used for reconstructing historical discharge